Kontribusi Sosiologi Dakwah dalam Menghadapi Generasi Milenial: Contribution of the Sociology of Da'wah in Facing the Millennial Generation - Ridwan, Ridwan; Mahmuddin (Litera Academica Publishing, 2025)
The rapid development of the digital era has significantly influenced the mindset, behavior, and daily lives of the millennial generation, who are often referred to as